Angiogenic Potential of Tissue Engineered Cartilage From Human Mesenchymal Stem Cells Is Modulated by Indian Hedgehog and Serpin E1 - Nossin, Yannick; Farrell, Eric; Koevoet, Wendy J. L. M.; Somoza, Rodrigo A.; Caplan, Arnold I.; Brachvogel, Bent; van Osch, Gerjo J. V. M. (Frontiers in Bioengineering and Biotechnology, 2020)
With rising demand for cartilage tissue repair and replacement, the differentiation of mesenchymal stem cells (BMSCs) into cartilage tissue forming cells provides a promising solution. Often, the BMSC-derived cartilage does not remain stable and continues maturing to bone through the process of endochondral ossification in vivo. Similar to the growth plate, invasion of blood vessels is an early hallmark of endochondral ossification and a necessary step for completion of ossification. This invasion originates from preexisting vessels that expand via angiogenesis, induced by secreted factors produced by the cartilage graft. In this study, we aimed to identify factors secreted by chondrogenically differentiated bone marrow-derived human BMSCs to modulate angiogenesis. The secretome of chondrogenic pellets at day 21 of the differentiation program was collected and tested for angiogenic capacity using in vitro endothelial migration and proliferation assays as well as the chick chorioallantoic membrane (CAM) assay. Taken together, these assays confirmed the pro-angiogenic potential of the secretome. Putative secreted angiogenic factors present in this medium were identified by comparative global transcriptome analysis between murine growth plate cartilage, human chondrogenic BMSC pellets and human neonatal articular cartilage. We then verified by PCR eight candidate angiogenesis modulating factors secreted by differentiated BMSCs. Among those, Serpin E1 and Indian Hedgehog (IHH) had a higher level of expression in BMSC-derived cartilage compared to articular chondrocyte derived cartilage. To understand the role of these factors in the pro-angiogenic secretome, we used neutralizing antibodies to functionally block them in the conditioned medium. Here, we observed a 1.4-fold increase of endothelial cell proliferation when blocking IHH and 1.5-fold by Serpin E1 blocking compared to unblocked control conditioned medium. Furthermore, endothelial migration was increased 1.9-fold by Serpin E1 blocking and 2.7-fold by IHH blocking. This suggests that the pro-angiogenic potential of chondrogenically differentiated BMSC secretome could be further augmented through inhibition of specific factors such as IHH and Serpin E1 identified as anti-angiogenic factors.